2002
DOI: 10.1159/000066671
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Memory in Alzheimer’s Disease

Abstract: A compelling feature of human memory is its striking capacity. Under certain circumstances, subjects can remember large amounts of information even with brief exposure at study. This investigation shows that this ability is preserved even in severely impaired Alzheimer’s disease patients, and this holds implications for the clinical management of amnesic patients. To this date, demonstrations of preserved learning and memory capacity in Alzheimer’s disease and amnesia have been confined to implicit memory task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The episodic memory deficit is usually portrayed by poor performance on recall and recognition measures indicative of impairment in encoding and storing information. Although recognition memory is often perceived as either spared or impaired following brain dysfunction, it can be assessed using a variety of procedures (e.g., yes/no, multiple choice, forced choice) yielding significantly different results (Bennett, Golob, Parker, & Starr, 2006; Karlsson, Johansson, Adolfsson, Nilsson, & Dubuc, 2003; Westerberg et al, 2006). Importantly, various methods of assessing episodic memory dysfunction may be sensitive to different underlying cognitive constructs and neuropathological processes (Jernigan, Ostergaard, & Fennema-Notestine, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The episodic memory deficit is usually portrayed by poor performance on recall and recognition measures indicative of impairment in encoding and storing information. Although recognition memory is often perceived as either spared or impaired following brain dysfunction, it can be assessed using a variety of procedures (e.g., yes/no, multiple choice, forced choice) yielding significantly different results (Bennett, Golob, Parker, & Starr, 2006; Karlsson, Johansson, Adolfsson, Nilsson, & Dubuc, 2003; Westerberg et al, 2006). Importantly, various methods of assessing episodic memory dysfunction may be sensitive to different underlying cognitive constructs and neuropathological processes (Jernigan, Ostergaard, & Fennema-Notestine, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have demonstrated that individuals are capable of recognizing substantial levels of information when forced-choice procedures are employed (Christensen, Kopelman, Stanhope, Lorentz, & Owen, 1998; Karlsson et al, 2003). Furthermore, in our clinical practice we have noted that individuals with mild AD tend to perform well on the forced-choice condition of the California Verbal Learning Test–Second Edition (CVLT–II), whereas patients with moderate-to-severe AD often do not.…”
Section: Introductionmentioning
confidence: 99%